How does neighbourhood socio-economic status affect the interrelationships between functioning dimensions in first episode of psychosis? A network analysis approach. (May 2021) - Izquierdo, Ana; Cabello, María; Leal, Itziar; Ayora, Miriam; Rodriguez-Jimenez, Roberto; Ibáñez, Ángela; Díaz-Marsá, Marina; Bravo-Ortiz, María-Fé; Baca-García, Enrique; Madrigal, José L.M.; Fares-Otero, Natalia E.; Díaz-Caneja, Covadonga M.; et al.
Abstract: The links between psychosis and socio-economic disadvantage have been widely studied. No previous study has analysed the interrelationships and mutual influences between functioning dimensions in first episode of psychosis (FEP) according to their neighbourhood household income, using a multidimensional and transdiagnostic perspective. 170 patients and 129 controls, participants in an observational study (AGES-CM), comprised the study sample. The WHO Disability Assessment Schedule (WHODAS 2.0) was used to assess functioning, whereas participants' postcodes were used to obtain the average household income for each neighbourhood, collected by the Spanish National Statistics Institute (INE). Network analyses were conducted with the aim of defining the interrelationships between the different dimensions of functioning according to the neighbourhood household income. Our results show that lower neighbourhood socioeconomic level is associated with lower functioning in patients with FEP. Moreover, our findings suggest that "household responsibilities" plays a central role in the disability of patients who live in low-income neighbourhoods, whereas "dealing with strangers" is the most important node in the network of patients who live in high-income neighbourhoods. These results could help to personalize treatments, by allowing the identification of potential functioning areas to be prioritized in the treatment of FEP according to the patient's neighbourhood characteristics. Highlights: Lower neighbourhood household income is associated with lower functioning. The role that each functioning domain plays could be different. Our results could have clinical and research implications.